Health awareness for women - Samant, Vatsala (Ed.) (New Delhi Gyan Publishing House, 2000)
Female of every species is created with one object and that is to propagate, her species. But while doing this natural task she is unaware of the hazards and may pay the price of becoming disabled and even facing the death. This book tells about the stage
Keywords: Health; Women-Health and hygine